Pengaruh Penerapan Standar Akuntansi Pemerintahan Terhadap Kualitas Penyajian Laporan Keuangan Pada Pemerintah Kabupaten Gorontalo: The Influence of the Implementation of Government Accounting Standards on the Quality of Financial Statement Presentation in the Gorontalo Regency Government - Sako, Umar; Lantowa, Felmi D (Universitas Muhammadiyah Sidoarjo, 2018)
This research analyzes and examines the effect of government accounting standards implementation on the quality of financial statements presentation in Gorontalo Regency Government. This research was conducted at Gorontalo Regency Government. Descriptive quantitative approach is applied i.e. it explains in the form of tables and graphs on the condition of objects and research results with the help of simple regression data analysis. Data was obtained through documentation and questionnaire on 40 employees / respondents by random sampling. The objective is providing information or knowledge about the effect of government accounting standards application of on the quality of financial statements presentation in Gorontalo Regency Government, as well as becoming an input and reference to take decisions regarding government accounting standards for the quality of presentation of financial statements. The results showed that the application of SAP has a positive effect on the quality of presentation of financial statements at the Office of Revenue Regional Finance and Assets Management (DPPKAD) in Gorontalo regency. The result of determination analysis shows that the dependent variable (quality of financial report) can be explained by independent variable (SAP implementation).